YBCO nanofibers produced by solution blow spinning doped with Ni and Zn at low concentrations - Ferreira Junior, Milton B [UNESP] (2025)
YBCO superconducting ceramic fibers doped with Ni or Zn were produced using the solution blow spinning (SBS) technique. Precursor solutions were prepared with acetates of yttrium, barium, copper, nickel, and zinc, and reduced and stabilized with polyvinylpyrrolidone (PVP) of different molar masses (360 000 g mol−1 and 1300 000 g mol−1). All reagents were dissolved in a solution with methanol, acetic and propionic acids. The samples were prepared with a stoichiometric ratio of YBa2Cu 3 − x M x O 7 − δ (M = Ni or Zn and x = 0.01, 0.02 and 0.04). The morphology of the samples was evaluated by scanning electron microscopy, revealing the formation of fibers on a sub-micrometer scale and an influence of the molar mass of PVP on the average fiber diameter. X-ray diffraction evidences the formation of the desired superconducting phase while not indicating the presence of the doping elements, supporting the idea that doping occurs at the copper site. This hypothesis is strengthened by the experimental observation that the critical temperature varies with x for both dopant materials. The observed properties are aligned with the expected behavior for samples produced by alternative methods, thus establishing SBS as a viable route to fabricate doped YBCO ceramic nanofibers.